Application of PQ4R Learning Model Using Picture Word Cards to Improve Beginning Reading Skills - Wahyuningsih, Nining; Nurasiah, Iis; Nurmeta, Irna Khaleda (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research aims to describe the application of the PQ4R learning model using picture word cards to improve beginning reading skills. This research took place at SDN Kandang Roda, located at Nanggewer Mekar RT 001 RW 002, Cibinong District, Bogor Regency, West Java. Participants in the research were 30 students. The research method used was classroom action research (PTK) Kemmis and Mc Taggart model research design which was carried out in two cycles. Each cycle consists of planning, implementation, action and observation, and reflection. Data collection techniques use initial reading practice tests, and non-tests in the form of observation, field notes and documentation. The data analysis technique used is qualitative. The improvement in initial reading skills after implementing the PQ4R learning model using picture word cards can be seen from the results of the pre-cycle completion percentage, namely 34%, cycle I was 69% and cycle II was 81%. In the pre-cycle to cycle I there was an increase of 35% and in cycle I to cycle II there was an increase of 12%, thus providing action through these two cycles can improve students' initial reading ability and each indicator has been achieved. And it has been proven that the application of the PQ4R learning model using picture word cards can improve the reading skills of beginning elementary school students in phase A (first grade).